Voluntary Private Investments Role in Pension System in Latvia - Dundure, Evija; Sloka, Biruta (Klaipeda University, 2019)
Pension systems have become one of the main priorities for the national governments. Developed countries population is getting older by putting the pressure on the state budgets and work age people tax load. The current pension system in Latvia performs according to regulation of state compulsory unfunded pension scheme since 1996 and regulation of the state funded or accumulated pension scheme since 2001. The third pension system pillar is private voluntary pension schemes realized in form of people contributions into pension funds and life insurance policies. Aim of the research – deeper analyses of voluntary private investments as the pension system part and its development challenges in Latvia. Research methods: scientific publications and previous conducted research analysis; analysis of time series on private pension fund developments in Latvia and comparisons with the situation in other OECD countries. The authors were looking for answer on the question – can voluntary private investments cover the gap between pre-retirement and after-retirement income of population in Latvia and what are the pre-conditions for it.
Keywords: voluntary savings; financial literacy; Bancassurance; pension system